Workplace Wellness Programs - Mattke, Soeren; Kapinos, Kandice; Caloyeras, John P.; Taylor, Erin Audrey; Batorsky, Benjamin (RAND Corporation, 2023)
This report leverages existing data on wellness programs to explore patterns of wellness program availability, employers’ use of incentives, and program participation and utilization among employees. The findings underscore the increasing prevalence of worksite wellness programs. Actual use of wellness programs remains limited, but may increase modestly with the use of monetary incentives. Evidence of cost savings is limited.